Crisis Concept Re-loaded?—The Recently Described Suicide-Specific Syndromes May Help to Better Understand Suicidal Behavior and Assess Imminent Suicide Risk More Effectively - Voros, Viktor; Tenyi, Tamas; Nagy, Agnes; Fekete, Sandor; Osvath, Peter (Frontiers in Psychiatry, 2021)
Background: Despite of the decreasing suicide rates in many countries, suicide is still a major public health concern worldwide. Traditional suicide risk factors have limited clinical predictive value, as they provide little reliable information on the acute psychological processes leading to suicide. Aims: The aim of this analysis is to describe and compare the recently introduced two suicide-specific syndromes (Acute Suicidal Affective Disturbance (ASAD) and Suicidal Crisis Syndrome (SCS)) with the classic psychological features of pre-suicidal crisis and also to assess the clinical utility of the new suicide prediction scales in contrast to classical risk factors. Method: Conceptual analysis. Results: Suicide-specific syndromes are not novel in terms of symptomatology or dynamics of symptom onset, but in their use of well-defined diagnostic criteria. In addition to symptomatic classification, they also provide an opportunity to objectively measure the current pre-suicidal emotional and mental state by validated tools. Limitations: Future studies need to be completed to prove the reliability and predictive validity of suicide-specific diagnostic categories and the related suicide risk assessment tools. Conclusion: Clinical use of suicide-specific syndromes is suggested. This transdiagnostic approach not only enables a more accurate and objective assessment of imminent suicide risk, but also facilitates research in neuroscience, which represent a major step forward in managing and complex understanding of suicidal behavior.